Factors affecting life-long reading habits of UiTM Johor students - Soo Kum Yoke, Carolyn; Mohd Anuar, Ahmad Azman; A/P Vasuthavan, Evelyn Sharminnie (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2008)
This study investigates the life-long reading habits of UiTM Johor students, specifically regarding reading for pleasure. The aim of this study is to examine the influence of factors such as oneself, peers, family, society, and modern devices in the cultivation of life-long reading habits. Data collected through a questionnaire (N=250) and structured interviews (N=50) provided valuable insights into the significant roles of these factors. The study revealed that both internal and external factors play a role in nurturing life-long reading habits. However, the most significant factor identified is society, which plays a crucial role in cultivating these habits. Thus, it is suggested that the role of society be emphasized to further nurture life-long reading habits.